2011
DOI: 10.1186/1423-0127-18-53
|View full text |Cite
|
Sign up to set email alerts
|

Postconditioning inhibits myocardial apoptosis during prolonged reperfusion via a JAK2-STAT3-Bcl-2 pathway

Abstract: BackgroundPostconditioning (PostC) inhibits myocardial apoptosis after ischemia-reperfusion (I/R) injury. The JAK2-STAT3 pathway has anti-apoptotic effects and plays an essential role in the late protection of preconditioning. Our aim was to investigate the anti-apoptotic effect of PostC after prolonged reperfusion and the role of the JAK2-STAT3 pathway in the anti-apoptotic effect of PostC.MethodsWistar rats were subjected to 30 minutes ischemia and 2 or 24 hours (h) reperfusion, with or without PostC (three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 21 publications
2
49
0
Order By: Relevance
“…The JAK2 inhibitor AG490 was associated with a significant reduction in GLP1-and TCF7L2-induced STAT3 phosphorylation. Downstream activation of AKT, which is induced by GLP1 and TCF7L2 in islets [4,6,26] and linked to STAT3 signalling [27], was also blocked by the JAK2 inhibitor (Fig. 7d).…”
Section: Resultsmentioning
confidence: 86%
“…The JAK2 inhibitor AG490 was associated with a significant reduction in GLP1-and TCF7L2-induced STAT3 phosphorylation. Downstream activation of AKT, which is induced by GLP1 and TCF7L2 in islets [4,6,26] and linked to STAT3 signalling [27], was also blocked by the JAK2 inhibitor (Fig. 7d).…”
Section: Resultsmentioning
confidence: 86%
“…We were among the first to report a Bcl-2 increase and cleaved caspase-3 decrease in PostC (274). It has been also reported that PostC may reduce myocardial apoptosis during reperfusion via a JAK-STAT-3-Bcl-2 pathway (355). Further studies focusing on other proteins of the Bcl-2 family may be helpful to define the long-term benefit of PostC against apoptosis (192,338).…”
mentioning
confidence: 82%
“…These studies suggest an important role in reperfusion-induced apoptosis. Both PreC and PostC limit reperfusion injury affecting all form of cell death, including apoptosis (6,274,355,392). Of course, reperfusion must be applied as soon as possible.…”
mentioning
confidence: 99%
“…The Bcl-2 family protein, Bax, is a pro-apoptotic protein, which forms complexes with other proteins in the mitochondrial outer membrane, promoting the release of pro-apoptotic molecules, including cytochrome C, and activates apoptosis (29). Bcl-2 is an anti-apoptotic molecule that reduces myocardial apoptosis during reperfusion (30). Bcl-2 inhibits the action of Bax through direct or indirect mechanisms and reduces cell death (31,32).…”
mentioning
confidence: 99%